Perceived Inventory of Technological Competency as Caring in Nursing (PITCCN): Psychometric Evaluation (International Journal of Studies in Nursing, 2019)
Background: The theory of Technological Competency as Caring in Nursing (TCCN) was developed by Locsin (2005) to guide the expression of “technological competency as caring in nursing” among practicing nurses. While the Technological Competency as Caring in Nursing Instrument (TCCNI) was developed and translated into other languages, no instrument measuring the TCCN among Japanese nurses was developed and tested. Thus, the Perceived Inventory of Technological Competency of Caring in Nursing (PITCCN) was developed and improved. Aim: The aim of this study was to validate the PITCCN using construct validity through structural equation modeling (SEM). Methods: The PITCCN is a four-factor questionnaire. The PITCCN was distributed to four hospitals (402 nurses) from selected Shikoku District in Japan. The theoretical model was tested using confirmatory factor analysis (CFA). Exploratory factor analysis and CFA via a SEM were used to justify construct validity, and Cronbach’s alpha coefficient was determined to establish reliability of constructs using SPSS and AMOS 25.0. Results: Finding shows that the chosen fit index test like Tucker Lewis Index (TLI), Goodness of Fit Index (GFI), and Normed Fit Index (NFI) are greater than 0.80 as set by the requirement. The values of the chi-square/degree of freedom (CMIN/DF), Comparative Fit Index (CFI), Incremental Fit Index (IFI), and Root Mean Square of Error Approximation (RMSEA) showed acceptable to good fit. Conclusion: GFI of the structure model was acceptable.